War, medicine and modernity - Cooter, Roger; Harrison, Mark.; Sturdy, Steve (Stroud : Sutton, 1998)
This volume presents the first scholarly assessment of the interconnections between war, medicine, society and modernity. Covering the period 1870 to 1945, this work emphasises the effects of warfare on the development of the modern world.
1. Of war, medicine and modernity: Introduction / Roger Cooter and Steve Sturdy -- 2. The Red Cross flag in the Franco-Prussian War: Civilians, humanitarians and war in the 'modern age' / Bertrand Taithe -- 3. Striving to be separate?: Civilian and military doctors in Cape Town during the Anglo-Boer War / Molly Sutphen -- 4. War as experiment: Physiology, innovation and administration in Britain, 1914-1918: The case of chemical warefare / Steve Sturdy -- 5. 'Soldier's heart': The redefinition of heart disease and speciality formation in early twentieth-century Great Britain / Joel D. Howell -- 6. Physicians and citizens: US medical women and military service in the first World War / Kimberly Jensen -- 7. Malingering in modernity: Psychological scripts and adversarial encounters during the first World War / Roger Cooter -- 8. Status, manpower and mental fitness: Mental deficiency in the first World War / Mathew Thomson -- 9. Sex, medicine and morality during the first World War / Lutz D.H. Sauerteig -- 10. Fighting militarism?: British nursing during the second World War / Penny Starns -- 11. Fighting research: Army participation in the clinical testing and mass production of penicillin during the second World War / Peter Neuschul -- 12. Disciplining the emotions: Fear, psychiatry and the second World War / Joanna Bourke.
Includes bibliographical references and index.
Keywords: 1800-1999; War -- Medical aspects; War and society; Civilization, Modern -- 20th century; Civilization, Modern -- 19th century; Sociology; Military Medicine -- history; History, 20th Century; Sociology; Warfare; sociology; Sociology; Civilization, Modern; War and society; War -- Medical aspects; Student Collection